LANDASAN ONTOLOGIS SOSIALISME - Wikandaru, Reno; Cahyo, Budhi (Jurnal Filsafat "WISDOM", 2016)
Socialism is an ideology assumed that shared ownership is the best way of life. Socialism did not proposed any private property because it makes people selfish and destroy the community harmony. Socialism wants the organization of production by the state as a suggestion to remove poverty and exploitation. Socialism proposed equal rights for all groups, and classes of people to enjoy prosperity, wealth and prosperity. The state has to secure as much as possible factor of production for the welfare of all the people, and not focused on personal well-being. Socialism assumes that the state is above public institutions that govern society selflessly. The key values in socialism is equality, cooperation, and compassion. The production is done on the basis of usability and not just for the profit. Competition replaced with planning. Every person working for the community and contribute to the common good so that it appears concern for others. Second, the underlying ontological foundation of socialism ideology associated with the ethical nature of man; human nature; and harmony of the society. The ideology of socialism found ethical nature of man is good; human nature is a social being; and assumes that there is harmony in the society.